999 ACUTE FRAILTY ASSESSMENT UNIT: A 6-MONTH QUALITATIVE STUDY OF READMISSIONS WITHIN 28 DAYS OF DISCHARGE & COLLECTIVE CASE ANALYSIS. (14th June 2022) - Hart, C; Shadbolt, L; Kaklamanos, M
Abstract: Introduction: Readmissions can have a negative impact on the care of frail individuals in regards to increased length of stay, healthcare-related harm, reduced quality of life and mortality. Review of frailty readmissions should lead to improvements of frailty care and clinical effectiveness. Method: We conducted a retrospective, qualitative analysis of readmissions of frail individuals discharged from our Acute Frailty Unit (AFU) over a six-month period. This is a collective case study in which we used instrumental cases to highlight specific learning points. We used the Electronic Patient Records database to measure the total number of readmissions related to AFU discharges. The Framework methodology was then utilised to further analyse and cluster cases. Common themes linked to readmissions and the time-to-readmission were studied, leading to structured (SMART) quality improvement interventions. Results: Four hundred and thirty individuals were discharged from AFU. Eighty-nine (21%) were readmitted within 28 days of index hospital admission. Fifty-eight percent (50/89) of individuals were readmitted to hospital (any ward) with a different presenting complaint compared to index admission. Twenty-two (25%) cases were readmitted with the same initial complaint, while nine (10%) experienced problems due to ineffective discharge planning. In eight (7%) cases, readmission was linked to healthcare-associated complications. Forty (45%, 40/89) individuals stayed at home for <7 days after their index discharge, whilst the remaining forty-nine (55%) returned to hospital after 7–28 days. Only eight (9%) readmissions were from care home settings. A bundle of SMART interventions has been developed, including post-discharge support with acute frailty clinics, enhanced frailty dietetic support and improved communication with community partners. Conclusion: (s) This collective case study shares important learnings related to the readmission patterns of acute frailty units. Individual case studies are essential in understanding the ways that patient-centred care should be tailored to become more effective.